HUBUNGAN PENGETAHUAN IBU PASANGAN USIA SUBUR DENGAN TES IVA DI WILAYAH KERJA PUSKESMAS PADANG PASIR - Sarah Fitria; Nevi Susianty; Nova Avianti Rahayu (Universitas Prima Indonesia, 2023)
Cervical cancer is one of the main causes of death for women. The incidence of cervical cancer in the world is 7.9% annually, in Indonesia in 2013 it was 10.3% and in Dr.M.Djamil Hospital Padang in 2015 it was 1.6%. One way to find out early detection of cervical cancer is by screening. Cervical cancer can be detected early with an IVA test. Achievement of the IVA test at the Padang Pasir Padang Health Center is still below the national target, which is only 5.6%. The aim of the study was to determine the relationship between the knowledge of PUS mothers and the implementation of the IVA test in the working area of ​​the Padang Pasir Health Center, Padang City. This research method is descriptive analytic with cross sectional design. The research was carried out in the working area of ​​the Padang Pasir Padang Health Center. The population in this study were women of childbearing age, the sampling technique was multistage random sampling with a total sample of 82 people. Data was collected using a questionnaire. Data analysis consisted of univariate and bivariate using the chi-square test. The results showed that 96.3% of respondents had good knowledge and 91.5% of respondents had never taken an IVA test. There is no knowledge relationship (p=1,000). The conclusion of this study is that there is no relationship between the knowledge of PUS mothers and the implementation of the IVA test